Pengaruh Kombinasi Fermentasi Cair Kulit Bawang Merah dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Selada Merah (Lactuca sativa var. Arista) di Dataran Rendah - Isti Fifit Zarokhmah; Muharam Muharam; Rommy Andika Laksono (Peneliti.net, 2021)
The soil laboratory tests showed that the expeimental land had a silty clay texture and had low macro and micro nutrients, so that fertilization treatment was needed to grow up the vegetable crops especially red lettuce. The purpose of this research is to find the best combination of liquid fermented onion peel and NPK fertilizer. This research was carried out on the land of Tambelang Bekasi, from July to September 2021. The research method used was an experimental method and the experimental design used was a Randomized Block Design (RAK) single factor consisting of 10 treatments and 3 replications. Data were analyzed using analysis of variance and further tests with Duncan Multiple Range Test (DMRT) at 5% level. The experimental results showed that combination of liquid fermented onion peel and NPK fertilizer have significantly different effects on the average plant height (35 HST), average number of leaves (28 and 35 HST), average stem diameter (14, 21, and 35 HST), average root length, average fresh weight per plant, average fresh weight per plots, average leaf area, average leaf area index. Treatment E (NPK Kujang 360 kg/ha + liquid fermented onion peel 50 ml/lt) gives the best result on the average plant height (21, 28 and 35 HST), average number of leaves (35 HST), average stem diameter (28 and 35 HST), average fresh weight per plant, average leaf area, and average leaf area index